2018
DOI: 10.17358/jma.15.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Learning Organization in order to Increase Supply Chain Performance in SPR Maju Bersama Bojonegoro

Abstract: Sekolah Peternakan Rakyat (SPR) Maju Bersama was formed 3 years ago. SPR Maju Bersama still has some weaknesses in terms of human resource and supply chain performance. Learning organizations are needed for organizations to form an organization that can continuously run independent learning process, so that it has a fast thinking and acting to respond any changes. Therefore, SPR has to implement the learning organization. This paper aims to identify the effect of learning organization on supply chain performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…In this study, it was found that learning organization can lead to supply chain driver. This finding is consistent with the findings of Ikhwan et al (2018), who also mentioned that the better implementation of the learning organization, the more optimal the supply chain driver is. These results further support the concept of knowledge, which can enhance adaptability in higherlevels learning, and the development of products, services, and technologies (Ramanathan et al 2011).…”
Section: Conclusion and Recommendations Conclusionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, it was found that learning organization can lead to supply chain driver. This finding is consistent with the findings of Ikhwan et al (2018), who also mentioned that the better implementation of the learning organization, the more optimal the supply chain driver is. These results further support the concept of knowledge, which can enhance adaptability in higherlevels learning, and the development of products, services, and technologies (Ramanathan et al 2011).…”
Section: Conclusion and Recommendations Conclusionsupporting
confidence: 92%
“…Another important finding is that the supply chain driver have a significant positive impact on supply chain performance, which is consistent with Ikhwan et al (2018). Control facilities is important in strategic planning by reducing facility costs (Shahzadi et al 2013).…”
Section: Conclusion and Recommendations Conclusionmentioning
confidence: 52%
See 2 more Smart Citations
“…Organizational sustainability can also be attained by maintaining organizational trust, which acts as a catalyst for employee involvement and leaders' role in creating open communication with subordinates (Ilyas et al 2020). Ikhwan et al (2018), said that the learning organization is still possible to be implemented in SPR Maju Bersama to maintain the continuity of its business.…”
Section: Introductionmentioning
confidence: 99%